2019
DOI: 10.1016/j.tibtech.2019.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Overlooked? Underestimated? Effects of Substrate Curvature on Cell Behavior

Abstract: People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 96 publications
(120 reference statements)
0
97
0
Order By: Relevance
“…Although other studies have also reported effects of curvature on several cell types including fibroblasts (31,95), osteoblastic cells (96,97) and MSCs (31)(32)(33), there is a lack of information regarding satellite cells, thus further investigation is still needed. With the increasing development of tools for the fabrication of micro-curved surfaces, more systematic and precise studies should be possible (98).…”
Section: Basic Requirements For Sc Adhesion and Proliferation On Mcsmentioning
confidence: 99%
“…Although other studies have also reported effects of curvature on several cell types including fibroblasts (31,95), osteoblastic cells (96,97) and MSCs (31)(32)(33), there is a lack of information regarding satellite cells, thus further investigation is still needed. With the increasing development of tools for the fabrication of micro-curved surfaces, more systematic and precise studies should be possible (98).…”
Section: Basic Requirements For Sc Adhesion and Proliferation On Mcsmentioning
confidence: 99%
“…Many epithelial tissues exhibit complex morphologies that are mostly dominated by curved surfaces such as those found in lung alveoli and intestinal villi (Torras et al, 2018;Baptista et al, 2019). These three-dimensional (3D) topographies generate gradients in biochemical signals and mechanical tension that play a key role in cell polarization, morphology, and function (Farin et al, 2016;Krndija et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While traditionally ignored in flat in vitro models, 3D topographies are distinctive elements in the emergence and further development of a new generation of tissue-engineered cell culture substrates (Griffith and Swartz, 2006). These 3D models are capable of capturing the complex physiological responses of tissue in vitro and have been employed to systematically study the effects of in vivo-like tissue geometry and curvature on cell fate (Griffith and Swartz, 2006;Baptista et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Kinematic descriptors such as speed, mean curvature, and angular speed exhibit were extracted and compared for a PS Petri dish, PLA disc or inside a device. The kinematic descriptors between the PLA substrate and the PS were very similar despite slight difference on the surface topology [25]. However, the diffusion coefficient that is typical of a kind of motion and not strictly related to the kinematics of individual cells is equal for the two videos, thus demonstrating that cells under the microscope have the same behaviour (Fig 5B.iv).…”
Section: Optical Properties Of Pla: Transparency and Autofluorescencementioning
confidence: 84%